2016
DOI: 10.12669/pjms.322.8737
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Implications of Blindness and Low Vision in students of Blind School Bahawalpur

Abstract: Objective:To find out the psychosocial implications of blindness and low vision in students of blind school Bahawalpur.Methods:A cross sectional descriptive study was carried out in Higher Secondary School for blind, Bahawalpur after getting approval from Institutional review board of Quaid-e-Azam Medical College, Bahawalpur and Principal of Blind School, Bahawalpur. Forty willing students filled a customized questionnaire, consisting of questions about logistic variables and questions regarding areas of satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 9 publications
2
30
0
1
Order By: Relevance
“…Children affected by visual impairment are more likely to experience social and economic disadvantage [7], and the impacts of reduced mobility and independence become an increasing problem as young adults progress into further and higher education. Severe visual impairment is associated with an increased risk of depression, anxiety and sleep disorders [8][9][10][11][12][13], and studies have also reported an increased risk of depression among caregivers of those with visual impairment [14,15]. It is estimated that the full lifetime cost of blindness in individuals with biallelic RPE65-mediated IRD in the UK is between £1.6 and £1.8 million.…”
Section: Disease Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Children affected by visual impairment are more likely to experience social and economic disadvantage [7], and the impacts of reduced mobility and independence become an increasing problem as young adults progress into further and higher education. Severe visual impairment is associated with an increased risk of depression, anxiety and sleep disorders [8][9][10][11][12][13], and studies have also reported an increased risk of depression among caregivers of those with visual impairment [14,15]. It is estimated that the full lifetime cost of blindness in individuals with biallelic RPE65-mediated IRD in the UK is between £1.6 and £1.8 million.…”
Section: Disease Backgroundmentioning
confidence: 99%
“…The average incremental costs over the simulated results were £611,203 and the average incremental QALYs were 6.4, giving a probabilistic ICER of £95,813; this is highly congruent with deterministic changes in costs and QALYs of £612,404 and 6.4, respectively. The proportion of simulations considered cost-effective when accounting for the additional QALY weighting for treatments with significant QALY gains (i.e., [10) was 71%.…”
Section: Probabilistic Sensitivity Analysismentioning
confidence: 99%
“…Our sample was summed up in 148 males and 119 female individuals from different primary and middle schools (aged [6][7][8][9][10][11][12][13][14][15] in Riyadh, Saudi Arabia. The sample were given the questionnaire and interviewed following the WHO oral health assessment form for children.…”
Section: Resultsmentioning
confidence: 99%
“…This may increase because of different feelings of inadequacy, facing difficulties in social interactions with people and making contacts. 13 In a study done on the visually impaired children in Riyadh, Saudi Arabia…”
Section: Medical Complications Of Visually Impairment Relevant To Denmentioning
confidence: 99%
“…Blindness can be caused by several ocular diseases, such as glaucoma,2 cataract,3 and globe injury 4. Blindness not only causes difficulties in daily life5 but also results in serious psychological problems (such as anxiety, sadness, and depression) for blind patients 6. Meanwhile, blindness also imposes a heavy economic burden on society.…”
Section: Introductionmentioning
confidence: 99%